Maddaddam - Atwood, Margaret 1939 (London Bloomsbury, 2013)
A conclusion to the MaddAddam trilogy finds Toby and Ren returning to the MaddAddamite cob house after rescuing Amanda and assuming the duties of the Craker's religious overseers while Zeb searches for the founder of the pacifist green religion he left years earlier.
"Bringing together characters from Oryx and Crake and The Year of the Flood, this thrilling conclusion to Margaret Atwood's speculative fiction trilogy confirms the ultimate endurance of humanity, community, and love. Months after the Waterless Flood pandemic has wiped out most of humanity, Toby and Ren have rescued their friend Amanda from the vicious Painballers. They return to the MaddAddamite cob house, which is being fortified against man and giant Pigoon alike. Accompanying them are the Crakers, the gentle, quasihuman species engineered by the brilliant but deceased Crake. While their reluctant prophet, Jimmy--Crake's one-time friend--recovers from a debilitating fever, it's left to Toby to narrate the Craker theology, with Crake as Creator. She must also deal with cultural misunderstandings, terrible coffee, and her jealousy over her lover, Zeb. Meanwhile, Zeb searches for Adam One, founder of the God's Gardeners, the pacifist green religion from which Zeb broke years ago to lead the MaddAddamites in active resistance against the destructive CorpSeCorps. Now, under threat of an imminent Painballer attack, the MaddAddamites must fight back with the aid of their newfound allies, some of whom have four trotters. At the center is the extraordinary story of Zeb's past, which involves a lost brother, a hidden murder, a bear, and a bizarre act of revenge. Combining adventure, humor, romance, superb storytelling, and an imagination that is at once dazzlingly inventive and grounded in a recognizable world, MaddAddam is vintage Margaret Atwood, and a moving and dramatic conclusion to her internationally celebrated dystopian trilogy"-
The MaddAddam trilogy: The story so far -- Egg : The story of the egg, and of Oryx and Crake, and how they made people and animals; and of the chaos; and of snowman-the-jimmy; and of the smelly bone and the coming of the two bad man -- Rope : Rope ; Procession ; Poppy -- Cobb House : Morning ; Breakfast ; Hammock ; Story ; Homecoming -- Bearlift : The story of when Zeb was lost in the mountains, and ate the bear ; The fur trade ; Crash ; Supplies ; Bunkie ; Bigfoot ; The story of Zeb and thank you and good night -- Scars : Scars ; Violet biolet ; Blink -- Zeb in the dark : Zeb in the dark ; The story of the birth of Zeb ; The petrOleum brats ; Schillizzi's hands ; Mute and theft ; Deeper into the pleeblands -- Snowman's progress : Floral besheet ; Girl stuff ; Snowman's progress ; Drugstore romance ; Weeding -- Blacklight headlamp : The story of Zeb and Fuck ; Floating world ; The hackery ; Cold dish ; Blacklight headlamp ; Intestinal parasites, the game -- Bone cave : Cursive ; Swarm ; Bone cave ; Farrow -- Vector : The story of how Crake got born ; Young Crake ; Grob's attack ; Vector ; Scales and tails ; The story of Zeb and the snake women -- Piglet : Guru ; Piglet ; Palaver ; Fallback ; Fortress AnooYoo -- The train to Cryojeenyus : The story of the two eggs and thinking ; Shades ; Kicktail ; Raspberry mousse ; The train to CryoJeenyus ; Lumiroses ; Edencliff -- Eggshell : Muster ; Sortie ; Eggshell ; The story of the battle -- Moontime : Trial ; Rites ; Moontime -- Book : Book ; The story of Toby.
114003
Keywords: Genetic engineering; Diseases; Epidemics; Dystopias; Apocalyptic fiction; Science fiction